An unusual case of uterine PEComa presenting with disseminated intravascular coagulation - Rodger Rothenberger; Amanda Jackson; Ady Kendler; Thomas Herzog; Caroline Billingsley (Elsevier, 2019)
Perivascular epithelioid cell neoplasms (PEComas) are mesenchymal neoplasms originating from the perivascular epithelioid cell (PEC) line. The World Health Organization (WHO) further defines PEComa as "a mesenchymal tumor composed of histologically and immunohistochemically distinctive perivascular epithelioid cells". Gynecologic PEComas account for approximately ¼ of the PEComa cases reported in the literature and are histologically characterized by stromal hyalinization with complete or partial circumscription with hyaline background and diffuse, small vessel vascularity (Musella et al., 2015). Uterine PEComas typically present with vaginal bleeding and/or a uterine mass, are managed surgically with resection, and can be followed by adjuvant treatment if indicated based on pathologic risk factors for aggression. Adjuvant therapy is not standardized given the rarity of these tumors, and can include chemotherapy, radiation, targeted therapy (mTOR inhibitors due to common gene mutations and a hypothesized pathophysiology of this neoplasm) and/or hormones. In this case report, we describe an unusual presentation for a uterine PEComa in a woman initially complaining of worsening cutaneous bruising and petechiae, found to be in florid disseminated intravascular coagulation (DIC) without a clear etiology. Ultimately her extensive hematology evaluation only found a large uterine mass that appeared to be a 9 cm fibroid. She underwent hysterectomy following recovery from her DIC, and was diagnosed with a large uterine PEComa. Keywords: PEComa, Uterine sarcoma, DIC, Aromatase inhibitor, mTOR inhibitor